2021
DOI: 10.1186/s40900-021-00262-5
|View full text |Cite
|
Sign up to set email alerts
|

More than a method: trusting relationships, productive tensions, and two-way learning as mechanisms of authentic co-production

Abstract: Background Knowledge mobilisation requires the effective elicitation and blending of different types of knowledge or ways of knowing, to produce hybrid knowledge outputs that are valuable to both knowledge producers (researchers) and knowledge users (health care stakeholders). Patients and service users are a neglected user group, and there is a need for transparent reporting and critical review of methods used to co-produce knowledge with patients. This study aimed to explore the potential of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 45 publications
3
91
0
Order By: Relevance
“…We found that it is possible to involve a range of stakeholders in developing such indicators, including women and men with lived experience of recurrent miscarriage. Participants in our study valued the opportunity to be involved and to discuss and learn from each other, being afforded the ‘space to talk’ [ 36 ], though perhaps some contributors did not feel that they brought equally important knowledge as others. As noted by Rushforth and colleagues [ 17 ], we found that, following lay explanations and rich discussions during the consensus meetings, parent advocates/support group representatives could rate complex recommendations/KPIs and often gave similar opinions as health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…We found that it is possible to involve a range of stakeholders in developing such indicators, including women and men with lived experience of recurrent miscarriage. Participants in our study valued the opportunity to be involved and to discuss and learn from each other, being afforded the ‘space to talk’ [ 36 ], though perhaps some contributors did not feel that they brought equally important knowledge as others. As noted by Rushforth and colleagues [ 17 ], we found that, following lay explanations and rich discussions during the consensus meetings, parent advocates/support group representatives could rate complex recommendations/KPIs and often gave similar opinions as health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…There is a whole terminology in how patients can be involved in research-knowledge sharing, authentic involvement, patient partner (PP) perspective, patient-oriented research (POR) and shared dialogue with co-production being shown as the gold standard. The most important factors in the success of PPI include 'the relationship between researcher and contributors, and particularly researcher willingness to change their approach in response to feedback' [8]. Patient involvement in research agenda setting is suggested to depend on 'the quality of attitude and engagement of researchers and funding agencies' [9].…”
Section: Introductionmentioning
confidence: 99%
“…Developing participant trust and openness is considered an important factor for successful co-production (Knowles et al, 2021). Preexisting power dynamics and assumptions about who knows best, what works best, and what others think and feel, can be a barrier to constructive communication (Farr et al, 2021).…”
Section: Creativity Trust and Powermentioning
confidence: 99%
“…Expert healthcare professional status and technical language may give some viewpoints and ideas an unfair advantage (Farr et al, 2021). All stakeholders possess valuable lived experience knowledge and ideas, but some lack the confidence or a method to clearly express them (Knowles et al, 2021). An additional challenge is surfacing deeper tacit and latent knowledge about people's values, feelings and creative ideas.…”
Section: Introductionmentioning
confidence: 99%